LEARNING MEDIA PHYSICAL EDUCATION BASED REVOLUTION 4.0 TO IMPROVE STUDENT LEARNING OUTCOMES THE COVID-19 PANDEMIC - Ari Mecky Prawira Ketaren (Indonesia Sport Journal, 2021)
Education 4.0 is an education characterized by the use of digital technology in the learning process, therefore android-based learning media can improve thematic learning outcomes carried out online. Android-based learning media is an application that contains material used by students in terms of learning. Researchers collected data through interview observations, surveys and blended learning methods. This research is the fifth grade students of SD Negeri 106790 Sei Menistrim for the Academic Year 2021/2022. Sampling was done by purposive sampling technique. That is by taking two classes taught by the same teacher. The initial conditions were obtained from daily test 1 with an average value of 75.00 as the control class using powerpoint learning media. While the average value of 87.00 as an experimental class using android-based learning media. By mastering android-based learning media, elementary school teachers can present Android-based learning as attractively as possible, which is related to the material to be studied and is the best solution when learning is carried out online and in accordance with the 4.0 revolution.Keywords: Learning Media, Revolution 4.0, Covid-9